Democratic decentralisation: experience of Karnataka - Abdul Aziz (2000)
This paper traces the evolution of rural local governance system in Karnataka, discusses its present structure and problems, and suggests a course of action for making these institutions more effective. The problem at the root of panchayats' troubles is that while power must be devolved to panchayats, higher level politicians are loath to yield any. - Reproduced
Keywords: Decentralization - India - Karnataka; Local government - India - Karnataka; Local government